2014
DOI: 10.5897/ajhc2013.0163
|View full text |Cite
|
Sign up to set email alerts
|

Poultry industry in the Wa Municipality of the Upper West Region of Ghana: Prospects and challenges

Abstract: The poultry industry is known to be a major contributor to Ghana's economy through employment creation and the enhancement of nutrition and food security. In spite of these contributions, the poultry industry is faced with a number of problems that necessitate solution. The study was conducted in the Wa Municipality of the Upper West Region of Ghana, with the prospects and challenges of the local poultry industry as its main objective. Ten poultry farmers were engaged as research participants using both struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…In addition, slaughtering, processing of intermediate and final products, and packaging for the cold room are performed. These and other activities are required for the success of the chicken business [55]. Consistently, previous studies have reported the same observations for labor in layer poultry farms across countries with economies under development [35,37,56], and thus agree with the results of this study for the layer poultry farms in Pakistan.…”
Section: Influence Of the Factors Under Studysupporting
confidence: 92%
“…In addition, slaughtering, processing of intermediate and final products, and packaging for the cold room are performed. These and other activities are required for the success of the chicken business [55]. Consistently, previous studies have reported the same observations for labor in layer poultry farms across countries with economies under development [35,37,56], and thus agree with the results of this study for the layer poultry farms in Pakistan.…”
Section: Influence Of the Factors Under Studysupporting
confidence: 92%